Pengaruh Capital Adequancy Ratio, Non Performing Loan, Tingkat Perputaran Kas, dan Biaya Operasional Pendapatan Operasional Terhadap Profitabilitas (Studi Pada LPD Se-Buleleng Barat Yang Terdaftar Pada Lplpd Periode 2014-2016) - Kadek Setia Budi; Made Arie Wahyuni (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2020)
This study aims to examine the effect of Capital Adequancy Ratio, Non Performing Loans, Cash Turnover Rate and Operating Costs Operating Income on Profitability. The research sample consisted of 57 Village Perredita Institutions, determined by the purposive sampling method. The data used is secondary data. Data analysis techniques using the classic assumption test, multiple linear regression tests such as t test, f test and the coefficient of derivation. The results showed (1) Capital Adequancy Ratio had a positive and significant effect on profitability with a value of t = sig 0.005, (2) Non Performing Loans had a negative and significant effect on profitability with a t-sig value of 0,000, (3) Cash turnover rate had a positive effect and significant to profitability with a value of t = 0.05, (4) Operating Costs Operating Income Profitability has a negative and significant effect on profitability with a value of t = 0.001, (5) Capital Adequancy Ratio, Non Performing Loans, Cash Turnover Rate and Operational Costs Operating Income simultaneous effect on profitability with a value of f = sig 0,000.